Association of DRD2/ANKK1 Taq1A polymorphism with depression in an open 45–64 year-old male population (international epidemiological HAPIEE and WHO MONICA programs) - V. V. Gafarov; E. A. Gromova; D. O. Panov; V. N. Maximov; I. V. Gagulin; A. V. Gafarova (Неврология, нейропсихиатрия, психосоматика)
Objective: to study the association of DRD2/ANKK1 Taq1A polymorphism with depression in an open 45–64-year-old male population from Novosibirsk.Patients and methods. A representative sample of an open 45–64-year-old male population (n=781) was surveyed within Screening IV of the international HAPIEE program and the WHO MONICA-psychosocial program in 2003–2005. All the study participants filled out the WHO MONICA-psychosocial Program Depression Scale. The DRD2/ANKK1 Taq1A C32806T (rs 1800497) polymorphism was genotyped using the published methods within the budgeting topic. The Pearson's chi-square (2) test was applied to test the statistical significance of differences between the groups. Significance in all types of analysis was taken at p ≤0.05.Results and discussion. The prevalence of depression in the open 45–64-year-old male population was 36.3%: 13.5% of the examinees had severe depression (SD) and 22.8% had moderate depression (MD). A comparative intergroup analysis showed that the odds ratio (OR) for the incidence of SD was 3.86 times higher in the T/C genotype carriers than in the C/C genotype ones, who, on the contrary, had no depression; the OR for the incidence of SD was also 3.28 times higher in the T/C genotype carriers, while MD was more common in the homozygous C/C genotype carriers. The OR for the incidence of SD was 2.63 times higher in the DRD2 T allele carriers than in the C allele carriers who did not suffer from depression in most cases.Conclusion. A significant association was established between the carriage of Taq1A (T allele) and depression in 45–64-year-old males.